MANAJEMEN LABA PADA PERUSAHAAN YANG MELANGGAR PERJANJIAN UTANG - Nurul Herawati (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2010)
This research aims to give empirical evidence concerning earnings management in firms violating debt covenant and to test whether earnings management in those firms are larger than that in control firms. Research population is manufacturing company listed at Bursa Efek Indonesia. The sample includes 17 firms violating debt covenant and 22 firms complying debt covenant as control firms. The sampling method is purposive sampling. Method of statistics used is t-test. The statistic test of first hypothesis shows that mean of discretionary accruals at a year before violation is significantly larger than that at the year debt covenant violation. This result supports debt covenant hypothesis. But, mean difference at the year of violation and at a year after violation does not provide the support for the hypothesis. The statistic test of second hypothesis shows that mean of discretionary accruals of firms violating debt covenant at a year before and at the year violation of debt covenant is significantly larger than that of control firms. Thus, we can conclude that violation of debt covenant motivate management to perform earnings management.